2016
DOI: 10.1155/2016/4870749
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Lower Limb Amputation in Patients with End-Stage Renal Failure on Dialysis: A Systematic Review

Abstract: Background. Renal dialysis has recently been recognised as a risk factor for lower limb amputation (LLA). However, exact rates and associated risk factors for the LLA are incompletely understood. Aim. Prevalence and risk factors of LLA in end-stage renal failure (ESRF) subjects on renal dialysis were investigated from the existing literature. Methods. Published data on the subject were derived from MEDLINE, PubMed, and Google Scholar search of English language literature from January 1, 1980, to July 31, 2015,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
3
18
1
Order By: Relevance
“…Although the difference was not significant, the prevalence of foot ulcers in patients with DM was 39.4% higher than in the group of patients without diabetes. The prevalence of amputation during this study, 8/66 (12.1%), is comparable with the range mentioned in the literature (1.7–13.4%) …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the difference was not significant, the prevalence of foot ulcers in patients with DM was 39.4% higher than in the group of patients without diabetes. The prevalence of amputation during this study, 8/66 (12.1%), is comparable with the range mentioned in the literature (1.7–13.4%) …”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of amputation during this study, 8/66 (12.1%), is comparable with the range mentioned in the literature (1.7-13.4%). 36 A previous study described that renal insufficiency is independently associated with a distal obstructive pattern of symptomatic lower-limb atherosclerosis. 37 Our results 38 Physical function is significantly lower in the group with foot ulceration than in the group without foot ulceration.…”
Section: Discussionmentioning
confidence: 98%
“…Although older age is a known risk factor for PAD among patients without ESRD, 1,22 the same may not be true for patients who receive dialysis. 8,10 In a study evaluating amputation trends among patients with ESRD from 1991 through 1994, the peak amputation rate occurred between 45 and 54 years of age for patients with diabetes and between 55 and 64 years of age for patients without diabetes. 12 Similarly, an international study of 29 838 patients receiving hemodialysis in the Dialysis Outcomes and Practice Patterns Study found that patients 65 to 74 years of age and those 75 years or older had significantly lower odds of amputation than patients 55 to 64 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that up to 95% of dialysis-treated diabetic patients are at high risk of foot problems, and HD itself is an independent risk factor for foot ulceration, non-healing, and amputation [ 15 , 16 , 17 ]. About 20% of DM patients will develop a FU one year after dialysis initiation, and they also have a higher incidence of new amputations and foot-related hospitalizations [ 18 , 19 , 20 ]. Risk factors, associated with the likelihood of developing a foot ulcer or lower limb amputation, other than DM, when in maintenance dialysis, are peripheral artery disease (PAD), peripheral neuropathy (PN), and coronary artery disease (CAD) [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%